Biomechanical report for the IAAF World Championships London 2017 shot put women's - Tucker, C.; Nicholson, G.; Cooke, M.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s shot put final took place on the night of August 9th in very wet weather conditions. Coming into the final, Lijiao Gong from China was the favourite as the world leader in 2017. Gong dominated the competition from the first round, whereby she provided a magnificent sequence of throws culminating with the gold medal throw in the fifth round measured at 19.94 m. The competition for the silver and bronze medal was hotly contested between Anita Márton from Hungary and Michelle Carter from the USA. The silver medal position swapped backwards and forwards between these two athletes over the first five rounds. However, in a dramatic finale Márton threw 19.49 m in the final round to snatch the silver medal. Michelle could not respond with her final throw of the competition and as such she obtained the bronze medal from her third round throw measured at 19.14 m. (Attention! registration on the IAAF site is required for downloading)